Study of predictors of hypoxemia in children with Pneumonia - Sah, HD (Journal of College of Medical Sciences-Nepal, 2014)
Objective To study the sign and symptoms of hypoxemia in children with pneumonia and to identify its clinical predictors in children between two months to five years of age. Methods Children between two to five years of age suffering from cough or difficult breathing were assessed. Arterial oxygen saturation was measured with a pulse oxymeter and child was labeled hypoxic if <90%. The children were categorized into four types according to WHO criteria-Cough and cold, pneumonia, severe pneumonia and very severe pneumonia. Results Out of 200 patients that were included in the study population, 101(51%) were found hypoxemic and was found in all grades of pneumonia. Frequency of hypoxemia increased with the severity of pneumonia being 100% for very severe pneumonia, 84% for severe pneumonia and 9% for pneumonia. None of the patients in the cough and cold category was found hypoxic. On univariate analysis, different predictors for hypoxemia found were inability to feed and drink, lethargy, tacypnoea, central cyanosis, chest indrawing and grunting. Discussion Prevalence of hypoxemia decreased with increasing age of the child. Significantly more number of infants (2–12months) were hypoxemic as compared to elder children. Conclusion Pneumonia in infants is risk factor for hypoxemia. Children less than one year with cough and difficult breathing were at more risk for hypoxemia. Prevalence and clinical predictors of hypoxemia validated WHO classification of pneumonia based on severity. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 1-8 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10230